Floppy's phonics book 12 - Hunt, Roderick (china, Oxford university press, 2011)
Level 2 Floppy's Phonics Sounds and Letters Books show all the sounds and graphemes from Phase 3 of Letters and Sounds in the context of Oxford Reading Tree scenes, packed with activities for practice and consolidation.